ISLAMIC FOUNDATIONS RELATIONSHIP TO THE CONCEPT OF SUSTAINABLE DEVELOPMENT (International Conference on Social and Islamic Studies, 2022)
In recent century, all nations have search how to reach sustainable development, its become the talk of conferences and other forums, regardless of their resources, societies and cultures. These countries have been looking for access to sustainable development goals, but few know that Islam has established principals of this task since first ages in the Qur'an and Sunnah. By reviewing from resources some of the legislation and morals in the Islamic religion. with respect to modern theories find that it laid the foundation stone for sustainable development. Can reach this conclusion by comparing Islamic legislation and the findings of the latest studies in order to reach sustainable development and it lead directly to the basic pillars of development. The Islamic curriculum included all the concepts of sustainable development and established for enhanced, advanced society with a high degree of sophistication and prosperity. Muslims only have to follow religious teachings, thus leading the nations.